Dual-wavelength Q-switched thulium-fluoride fiber laser for S+/S band using molybdenum disulfide (MoS2) as a saturable absorber. (28th April 2017) - Ahmad, H; Reduan, S A; Safaei, R
Abstract: In this work a Q-switched, dual-wavelength fiber laser is proposed and demonstrated for S+/S band operation. The proposed laser combines a 14.5 m long thulium-fluoride fiber with an absorption rate of 0.15 dB m −1 at a wavelength of 1400 nm with a 0.5 cm-long photonics crystal fiber to generate the desired dual-wavelength output in the S  +  /S band region. The generated output is then Q-switched using a compact MoS2 -based saturable absorber. A dual-wavelength output with lasing wavelengths at 1473.6 and 1479.3 nm is obtained. The pulses have a repetition rate and pulse width of approximately 15.9 kHz and 4.1 µ s at a maximum pump power of 126.4 mW, as well as a maximum average output power and pulse energy of 1.3 mW and 83.7 nJ at the same pump power. The generated pulses have a 3 dB bandwidth of 4.7 µ s, along with a signal-to-noise ratio of 32.0 dB. The proposed laser is able to transmit within the S-band transmission region or shorter, thus making it highly viable for a multitude of photonics applications.